The Impact of Intellectual Capital Efficiency on Bank Risks: Empirical Evidence from the Saudi Banking Industry - Alrashidi, Abdulelah; Alarfaj, Omar (International Journal of Economics and Financial Issues, 2020)
The main purpose of conducting this research is to investigate the impact of intellectual capital efficiency (ICE) and its components – human capital efficiency (HCE) and structural capital efficiency (SCE) - on bank credit and insolvency risks in the Saudi banking industry. To assess such a relationship, value added intellectual coefficient model (VAIC) along with a couple of panel data techniques were utilized by using quarterly observations spanning from the first quarter of 2009 to the fourth quarter of 2018. The carried out empirical results confirm the existence of a significant negative relationship between ICE, in particular HCE, and bank credit and insolvency risks. Keywords: Intellectual Capital Efficiency, Human Capital, Structural Capital, Credit Risk, insolvency risk, risk management JEL Classifications: O34, E24, J21, G32, C23, G21 DOI: https://doi.org/10.32479/ijefi.9959